Journalistic Representation in the Film Vina: Sebelum 7 Hari Regarding the Issue of Bullying in Indonesia: A Social Critique - Ritonga, Rohani; Saragih, Yoserizal (Journal Analytica Islamica, 2025)
The film Vina: Sebelum 7 Hari portrays the true story of a teenage girl from Cirebon who became a victim of bullying that ultimately led to her death. This film serves not only as a medium of entertainment but also as a tool for social advocacy, raising public awareness about the dangers of bullying. Through a journalistic approach, the film presents a powerful visual representation of the psychological and social impacts of bullying, as well as the role of the media in shaping public perception.This study employs a semiotic analysis method based on John Fiske's perspective to examine how the film represents sexual violence against women and its effects on public perception. The findings reveal that the film features two scenes of sexual violence, which, when analyzed through semiotic theory, depict the realities of sexual violence, critique societal norms, illustrate patriarchal dominance, and highlight social apathy—all reflected through reflective, intentional, and constructionist representations.Moreover, the film also emphasizes the phenomenon of "trial by social media" that occurred following the circulation of the video depicting Vina’s harassment. This demonstrates how social media can act as a double-edged sword in the pursuit of justice, while also illustrating how both mass and social media influence public opinion regarding issues of bullying and sexual violence.Through strong journalistic representation, this film not only exposes the harsh reality of bullying cases but also encourages the public to be more critical in responding to social issues in the digital era.